2020
DOI: 10.1016/j.ijhcs.2019.102383
|View full text |Cite
|
Sign up to set email alerts
|

Measuring perceived challenge in digital games: Development & validation of the challenge originating from recent gameplay interaction scale (CORGIS)

Abstract: Challenge is a key element of digital games, but a clear conceptualisation and operationalisation of this player experience were long missing. This made it hard for game developers to design for a well-balanced experience across different skill-sets, and impeded the synthesis of challenge-related games research. To overcome this, we introduce a systematic, extensive, and reliable instrument to evaluate the level of players' perceived challenge in digital games. We conceptualise challenge based on a survey of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 32 publications
0
56
0
2
Order By: Relevance
“…However, video games are a diverse medium that allows for a range of nuanced and subtle experiences besides fun -video games may also aford profound emotional experiences [33,37,42]. Over the past few years, emotional player experiences have received increasing attention within PX research, addressing topics such as emotionally moving [6] and emotionally challenging moments [8,20,48], discomforting experiences [13,28], and emotional attachment to game characters [7]. These works [6-8, 28, 48] are particularly concerned with the specifc emotions players feel (or at least report feeling) while playing, ranging from awe and respect to sadness, regret, and disgust.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…However, video games are a diverse medium that allows for a range of nuanced and subtle experiences besides fun -video games may also aford profound emotional experiences [33,37,42]. Over the past few years, emotional player experiences have received increasing attention within PX research, addressing topics such as emotionally moving [6] and emotionally challenging moments [8,20,48], discomforting experiences [13,28], and emotional attachment to game characters [7]. These works [6-8, 28, 48] are particularly concerned with the specifc emotions players feel (or at least report feeling) while playing, ranging from awe and respect to sadness, regret, and disgust.…”
Section: Related Workmentioning
confidence: 99%
“…video games that have a profound emotional impact on the player in the form of complex, mixed-afect experiences, -has grown in HCI games research. Existing work has looked at player experiences ranging from emotionally challenging [8,16,20] and discomforting experiences [13,28] to emotionally moving moments [6]. Others have addressed how games aford emotional [33] and deep [51] experiences, and developed ideation tools to facilitate the design for such experiences [49].…”
Section: Introductionmentioning
confidence: 99%
“…Achieving a state of “flow” is an overarching aim of games (Csikszentmihalyi & Csikszentmihalyi, 1988; Ke, 2016), and the provision of optimal challenge within the game is crucial to this eg, through matching the game difficulty and the players' skill level (Denisova et al., 2017; Hamari et al., 2016; Kim & Ruipérez‐Valiente, 2020). Although the terms challenge and difficulty can often be used interchangeably, they are interrelated yet distinct concepts— difficulty can be defined as the “probability of task failure” (Lomas et al., 2017), whereas challenge is a more nuanced and harder to define concept based on player perception of effort and experience ie, how difficult do they find the game, which depends on a player's particular skills and prior expertise (Denisova et al., 2020). Within the context of learning, tasks that are too difficult can result in cognitive overload whereas simple tasks may lead to feelings of boredom and disengagement (Hendrix et al., 2018; Shute et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gamers play on dedicated gaming consoles and on personal computers in their homes, but also on tablets and smartphones out in the world, and in dedicated gaming spaces (Entertainment Software Association, 2019 ). Research has demonstrated that people play digital games as a leisure activity to experience enjoyment (Boyle et al, 2012 ), escapism (Grove et al, 2016 ), immersion (Jennett et al, 2008 ), and challenge (Denisova et al, 2020 ), but gaming also provides more than just a pleasurable pastime. Playing digital games has also been shown to nurture wellbeing by helping players recover from daily stressors (Reinecke, 2009 ; Collins et al, 2019 ), repair noxious moods (Bowman and Tamborini, 2012 ), cope with life's challenges (Iacovides and Mekler, 2019 ), and practice emotional regulation (Granic et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%